The Effectiveness of Bank Financing to the Productivity of Agriculture Sector in South Sumatera - Achmad Soediro; Inten Meutia; Liliana . (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2017)
Purpose – This study aims to identify the effect of financing provided by banks (both conventional and Islamic bank) to the productivity in the agricultural sector in South Sumatera. This study analysed the forms and mechanisms of finance used by bank in order to find out whether the financing provides the benefit effectively in supporting the productivity of the agricultural sector in South Sumatra or not.Design/methodology/approach – The research used the preliminary data to trace the number of the debtor farmers. The data is from both conventional and Islamic banks in South Sumatera which distributed financing product to MSMEs in Agriculture sector. The secondary data collection was obtained from the banks while primary data was grounded from farmers both through the structured questionnaires and the depth interview. The analysis of this research is in both the descriptive quantitative and the qualitative methods.Findings – The financing in the agricultural sector in South Sumatra is relatively effective for farmers both in terms of increasing their financial gains and in terms of expanding the agricultural property.The results of this study are expected to give the significant figure about how far the financing product of the banks contributes to the increase of productivity of the agricultural sector in South Sumatera.Research limitations/implications – Effectiveness is analyzed by qualitative and descriptive quantitative methods in general, not included in the analysis per farmer. In addition, this study does not use financial ratios in measuring the effectiveness of the provision of financing.Originality/value – The effectiveness of financing in the agricultural sector, especially in sharia banking in Indonesia is still relatively minimal. This research is one way to initiate research which is expected to contribute to the implementation of wider sharia financing in the agricultural sector which now seems not to be the priority of the sharia banking sector in Indonesia.